STRATEGI PENGEMBANGAN USAH MIKRO KECIL MENENGAH (UMKM) LYNDA SNACK DI KECAMATAN NGABANG KABUPATEN LANDAK - Jumbri, Jumbri; Dolorosa, Eva; Maswadi, Maswadi (Universitas Galuh, 2023)
The economy, including micro, small, and medium-sized enterprises (MSME) actors who significantly contribute to enhancing people's welfare and the national GDP, will always be the subject of discussion. The necessity of developing Lynda Snack SMEs in a way that makes them competitive by putting in place appropriate strategies tailored to their circumstances Using SWOT analysis (strengths, weaknesses, opportunities, threats), the purpose of this study is to determine the development strategy for Lynda Snack Micro, Small, and Medium Enterprises (MSMEs) in the Ngabang District, Landak Regency. Descriptive qualitative research is used in this study. Purposive sampling was used to select the informants. Guidelines for interviews and questionnaires were used to conduct structured in-depth interviews for the purpose of data collection. The EFAS score is 2.66, and the combined IFAS score is 1.75. The development strategy is in quadrant I (growth-oriented strategy) or S-O, which indicates that Lynda Snack's MSMEs are in a very advantageous position. with their strengths and opportunities, allowing them to take advantage of current opportunities. Expanding the reach of product marketing in order to boost sales volume, creating business and employment opportunities, increasing collaboration and promotion of MSME Lynda snack products, and increasing the quality and quantity of sales products are all methods of carrying out the strategic focus.